A State-of-the-Art Review of Sharing Economy Business Models and a Forecast of Future Research Directions for Sustainable Development: A Bibliometric Analysis Approach - Duan, Carson (Sustainability, 2023)
The area of sharing economy business models (SEBMs) is expanding worldwide. To date, a few qualitative literature reviews concentrating on specific business models have been undertaken, while several have focused on the general concept of the sharing economy. Meanwhile, there is a lack of quantitative reviews in this area. Therefore, a retrospective review of the evolution of the SEBM area and prospective forecasts based on quantified data are urgently needed. In order to fill the gaps and critically evaluate the extant literature on the SEBM area and its scientometrics-related topics, this paper combines the Scopus and Web of Science databases to establish a dataset for a thorough bibliometric analysis. With 951 studies from 552 sources identified, this research provides comprehensive and nuanced information covering the most influential authors and their contributions to the subject, impactful articles with their citation details, ranked sources with their h_, g_ and m-index as well as collaboration maps for authors, affiliations and countries. Graphical representation of knowledge mapping depicts the evolution of publications over time and the emerging trends of current interests and potential directions for future research for sustainable development. This study revealed that Sustainability is the most relevant and second most impactful journal in SEBM research. More importantly, this research deployed keyword dynamic and thematic evolution to detect the current and future trending topics, providing seven future research directions: (1) drivers-, location- and competition-related topics; (2) SEBMs in emerging economies; (3) country-, region- and culture-oriented SEBMs; (4) the link between e-commerce and social media frameworks and SEBMs; (5) sustainability and SEBMs; (6) new technologies and SEBMs and (7) COVID-19 effects on SEBMs. Overall, the results of this study theoretically enrich the sharing economy business model literature and have substantial implications for policymakers and practitioners.